Organization enhances collective vigilance in the hovering guards of Tetragonisca angustula bees. (12th June 2018) - Shackleton, Kyle; Alves, Denise A; Ratnieks, Francis L W
Abstract : Many animals display vigilance behaviors in order to detect predators. We found that the guards of a social bee coordinate their vigilance, which increases nest defense. Guards hover and distribute themselves evenly around the nest entrance. This increases the group's field of view and ability to detect predators. We discuss how and why this organized pattern might arise. Abstract: One benefit of group living is vigilance against predators. Previous studies have investigated the group size effect, where individual vigilance decreases as group size increases without reducing the overall ability of the group to detect predators. However, there has been comparatively little research on whether the positioning of individuals can improve the collective vigilance of the group. We studied the coordination of vigilance and its effect on predator detection in the eusocial bee Tetragonisca angustula . Nests are defended by hovering guards that detect and intercept intruders before they reach the nest entrance, in addition to those that stand upon it. We show that hovering guards are positioned nonrandomly, with a strong tendency for equal numbers on both sides of the entrance. This organization increases the collective vigilance of the guard group, as groups distributed in an even ratio, either side of the entrance, have a greater collective field of view than groups that deviate from an even ratio. Finally, we use a bioassay to show that when guards are on both sides of the entrance, their ability to detect intruders before they reach the entrance increases. Overall, our results provide strong evidence that vigilance is coordinated and that this improves nest defense. Although other group-living animals are often selfish in their individual vigilance behaviors and face competing time constraints such as foraging, the altruistic nature of eusocial insect workers has probably facilitated the evolution of coordinated vigilance, as documented here in T. angustula .